Juvenal and the satiric genre - Jones, Frederick, 1955- (Classical literature and society., 2007)
"While claiming to stand outside literature altogether, Roman verse satire was the most aggressively literary of Roman genres, Juvenal's particularly so. In the opening lines of the corpus, his performance creates an arena in which the various genres of his Graeco-Roman cultural inheritance jostle to be heard, and are suppressed by his own generic identity." "In Juvenal and the Satiric Genre Frederick Jones considered the fluid nature of the generic field, and how Juvenal comes out of and fits into it. Specifically, it measures his use of names, his ambiguous and sometimes hostile relations with other genres, especially the queen of genres, epic, against his inherited and stated aim (of criticizing malefactors by name), and considers how the aspect of performance impinges on his multi-faceted satiric voice."--Jacket